PENGARUH KOMITMEN ORGANISASI, STRES KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Linda Rahmawati; Nurwanti Nurwanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
High turnover intention is one of the conditions that can harm the company or organization. This study aims to examine the effect of turnover intention with organizational commitment, job stress, and job satisfaction on employees of PT Sicepat Ekspres Cabang Setu. The sample in this study were 63 employees. Saturated sampling technique was used in this study in sampling. This study used a questionnaire to collect data. The data analysis method used is multiple linear regression. Data were analyzed by testing research instruments, classical assumptions, model testing, and hypothesis testing using statistical software.The results of the analysis show that organizational commitment, job stress, and job satisfaction have an effect on turnover intention. So that PT Sicepat Ekspres Setu Cabang Setu needs to pay attention to the level of organizational commitment, job stress and employee job satisfaction as an effort to reduce the level of employee turnover intention.